Beck and the great berry battle - Driscoll, Laura; Clarke, Judith (New York : Random House Children's Books, 2006)
Beck, a fairy, has a talent for talking to animals, but that may not be enough when she tries to mediate a war between the hummingbirds and the chipmunks
"A Stepping Stone Book."
Keywords: War -- Fiction; Reconciliation -- Fiction; Fairies -- Fiction; Chipmunks -- Fiction; Hummingbirds -- Fiction